The Effect of Social Media Marketing Activities and Price Perception on Brand Trust, Brand Image, and Purchase Intention - Abdul Haeba Ramli; Annisa Nur Aristawidya; James Ronald O. Mesina (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study explores direct and indirect effects with data collection methods through surveys by distributing questionnaires. The population in this study is a woman who uses barenbliss cosmetic products for at least 18 years. Based on the research results, 6 hypotheses can be accepted, namely The results of this study indicate that social media marketing activities have a positive effect on purchase intention, social media marketing activities have a positive effect on brand trust, social media marketing activities have a positive effect on brand image, price perception has a positive effect on brand image, brand trust has a positive effect on purchase intention, brand trust has a positive effect as a mediation on the relationship between social media marketing activities and purchase intention. A total of 4 hypotheses were rejected which showed no effect including, price perception and brand image have no effect on purchase intention, brand image has no effect on the relationship between price perception and purchase intention, brand image has no effect on the relationship between social media marketing activities and purchase intention. This research provides managerial implications for the marketing sector of a company to optimize social media strategies to create consumer purchase intention. Keywords: Social media marketing activities, price perception, brand trust, brand image, purchase intention